Search for excited muons in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. -L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Soc, 2006)
We present the results of a search for the production of an excited state of the muon, mu(*), in proton antiproton collisions at root s =1.96 TeV. The data have been collected with the D0 experiment at the Fermilab Tevatron Collider and correspond to an integrated luminosity of approximately 380 pb(-1). We search for mu(*) in the process p (p) over bar ->mu(*)mu, with the mu(*) subsequently decaying to a muon plus photon. No excess above the standard model expectation is observed in data. Interpreting our data in the context of a model that describes mu(*) production by four-fermion contact interactions and mu(*) decay via electroweak processes, we set a 95% confidence level production cross section upper limit ranging from 0.057 to 0.112 pb, depending on the mass of the excited muon. Choosing the scale for contact interactions to be Lambda=1 TeV, excited muon masses below 618 GeV are excluded.